2022
DOI: 10.1111/jan.15372
|View full text |Cite
|
Sign up to set email alerts
|

Nurse preceptors' experiences of promoting and teaching fundamental care to undergraduate nursing students: A qualitative study

Abstract: Aims To explore nurse preceptors' experiences in promoting and teaching the delivery of fundamental care to nursing students during their clinical period at nursing homes. Design The study used a qualitative descriptive approach. Methods Nine in‐depth, semistructured interviews were conducted with clinical nurses employed at five different nursing homes. Data collection lasted from September 2020 to April 2021. The interviews were recorded and transcribed verbatim. Inductive, qualitative content analysis was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Critical care settings are distinct health service workplaces that provide high staffing ratios, advanced monitoring, and organ support to improve patient morbidity and mortality to critically ill patients who either suffer from life-threatening conditions or are at risk of developing them (Jackson & Cairns, 2020). The factor that influences well-being, health, and patient outcomes affect patient satisfaction, nursing care quality, and changes in patients' plans to return to the institution for care, all of which are important indicators of quality services (Assefa et al, 2022), results in actual adverse occurrences that have an impact on the standard of care and patient safety (e.g., errors in medication administration, falls, decubitus ulcers and hospital-acquired infections), poor outcomes among nurses (e.g., low work satisfaction, high turnover intention, work stress, job burnout and increased absenteeism) and, ultimately, adverse organizational outcomes (Stănesu-Yadav & Lillekroken, 2023).…”
Section: Associated Factors In Caring Behaviour Among Nursesmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical care settings are distinct health service workplaces that provide high staffing ratios, advanced monitoring, and organ support to improve patient morbidity and mortality to critically ill patients who either suffer from life-threatening conditions or are at risk of developing them (Jackson & Cairns, 2020). The factor that influences well-being, health, and patient outcomes affect patient satisfaction, nursing care quality, and changes in patients' plans to return to the institution for care, all of which are important indicators of quality services (Assefa et al, 2022), results in actual adverse occurrences that have an impact on the standard of care and patient safety (e.g., errors in medication administration, falls, decubitus ulcers and hospital-acquired infections), poor outcomes among nurses (e.g., low work satisfaction, high turnover intention, work stress, job burnout and increased absenteeism) and, ultimately, adverse organizational outcomes (Stănesu-Yadav & Lillekroken, 2023).…”
Section: Associated Factors In Caring Behaviour Among Nursesmentioning
confidence: 99%
“…While impacting the quality of patient care, researchers worldwide found that the relationship between patients' satisfaction and the quality of patient care is critical in evaluating the quality of nursing care (Jagoda et al, 2019). Sometimes, evaluating, assessing, and understanding the effect on the patient's satisfaction is difficult after the nurses have been performing caring behaviour (Stănesu-Yadav & Lillekroken, 2023).…”
Section: Associated Factors In Caring Behaviour Among Nursesmentioning
confidence: 99%
“…Vygotsky defined the ZPD as "the distance between what a learner can do and a proximal level of what they may attain through guidance and collaboration with a more knowledgeable other". [5,8] Students learn new skills under the guidance of teachers or parents, and they can transfer them from their learned-skill zone to a new experiential zone of learning.…”
Section: Background 211 History Foretold On Brain-based Learningmentioning
confidence: 99%
“…In this period, students go beyond their classroom learning to apply their knowledge and skills to a real-life clinical setting. Clinical instructors play a significant role in preparing practice-ready nurses [3][4][5] and engage nursing students in the clinical learning process. Thus, clinical instructors hold responsibility for identifying their students' learning needs and ensuring they have a meaningful experience in their clinical practicum which can often be challenging as they attempt to keep students engaged at clinical site learning.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, para formar profissionais qualificados e que possam atender às necessidades de pacientes com situações de saúde complexas, há a necessidade de preceptores altamente qualificados e comprometidos (Stănesu-Yadav;Lillekroken, 2023). Nesse ínterim, responsabilidades, atitudes, papéis, habilidades, competências e características do preceptor tem sido apontadas na literatura.…”
Section: Introductionunclassified